(untitled) (Revista científica Olimpia, 2019)
This article intends to present the essential results of the study carried out in Volleyball team "Amigos do volvo do Lubango", Angola. The objective of this work is to support the role of the shoulder bursitis rehabilitation process in volleyball athletes, to give value to physical exercises, with an integrative character in the Therapeutic and Prophylactic Physical Culture. The investigation is carried out from the need to guarantee a proposal of exercises that allow to rehabilitate the Shoulder Bursitis in Volleyball athletes and the acquisition of a greater knowledge on the part of the management team of the possible alternatives to plan in its trainings to avoid injuries, will facilitate the stabilization of athletes in training and competitions, translating their benefits into people and society to ensure their health and the possibilities of sports results.